Capitalism, the bourgeoisie, the managers and their relations with the proletariat (Research, Society and Development, 2019)
The objective of the present work was to analyse and discuss topics related to capitalism, represented by the bourgeoisie and managers, in front of the class of the proletariat. The methodology used was of a qualitative / analytical nature, using works with strict adherence to the theme, obtained through bibliographical surveys. In these analyses, it was deduced that capitalism still represents an economic system based on the production of goods for the sole purpose of sale, implying processes of creation, production and market, causing capital to always be recycled in the productive chain. However, considering that this system is constituted by three social classes represented by capitalism, subdivided into two classes, the bourgeoisie and the managers; and a third class, the proletariat; it should be noted in this context, the emergence of new managers. In conclusion, in these reflections on capitalism, bourgeoisie, managers and proletarians, there is the great desire of the proletariat to overcome the bourgeoisie, reducing capitalism to formulate a new self-managed system of collective production, which allows the emergence of new managers.